(untitled) (Washington, D.C., 2005)
The book includes the activities reinforce vocabulary or give students practice listening, thinking, speaking and writing, but the underlying goal of all activities is to produce a smile and awareness that communicating in English has a lighter side and a potential for fun.
Keywords: English language; Study and teaching,Foreign speakers